Formal modelling and discrete-time analysis of BPEL web services. (10th March 2009) - Mateescu, Radu; Rampacek, Sylvain
Web services are increasingly used for building enterprise information systems according to the Service Oriented Architecture (SOA) paradigm. We propose in this paper a tool-equipped methodology allowing the formal modelling and analysis of web services described in the BPEL language. The discrete-time transition systems modelling the behaviour of BPEL descriptions are obtained by an exhaustive simulation based on a formalisation of BPEL semantics using the Algebra of Timed Processes (ATP). These models are then analysed by model checking value-based temporal logic properties using the CADP toolbox. The approach is illustrated with the design of a web service for GPS navigation.